Kontribusi Gaya KepemimpinansKepala Sekolah, Lingkungan Fisik Sekolahsdan Komitmen Gurusterhadap KinerjasGuru SekolahsDasar di KecamatansNogosari KabupatensBoyolali - Sulistiyawan, Sulistiyawan; Maryadi, Maryadi; Fathoni, Achmad (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
The specific purpose of this study was to analyze the contribution of the principal's leadership style, the physical environment of the school, and the teacher's commitment to the performance of primary school teachers in Nogosari District, Boyolali Regency. This type of research is quantitative research. The research was conducted in an elementary school in the District of Nogosari, Boyolali Regency. The population in this study were 333 teachers. A sample of 182 teachers. The results of the significance test of the contribution of the principal's leadership style, school physical environment and teacher commitment to teacher performance obtained F count (131.961) > F table (2.70) it can be concluded that there is a joint contribution between the principal's leadership style, school physical environment and teacher commitment to teacher performance. The results of the study prove that there is a contribution from the principal's leadership style to teacher performance, the school's physical environment to teacher performance, and teacher commitment to teacher performance.